Mysidacea collected by the Soviet Antarctic Expedition on the M/V "Ob". - Birstein, J. A.; Tchindonova, J. G. (Biol. Rep. Soviet Antarct. Exped. (1955-1958), 1962)
M1203
from NeMys (TI150.pdf); NeMys doc_id: 282